PASIEN PALIATIF KANKER DAN KELUARGA PASIEN PENTING MENDAPATKAN PELAYANAN PENDAMPINGAN DAN KONSELING PASTORAL - Marfan Ferdinanda Tahamata; Tony Tampake (POIMEN Jurnal Pastoral Konseling, 2024)
Pastoral assistance and counseling services are provided for those who are in a weak situation and condition, both physically, psychologically, socially and spiritually, as is done for palliative cancer patients. The aim is for cancer palliative patients to be able to face and overcome the pain they are experiencing with inner calm. However, reality shows that patient families also need pastoral care and counseling services, because patient families also experience a weak situation when a member of their family experiences cancer. One of the impacts experienced by the patient's family is that they experience deep sadness. If pastoral care and counseling services are not immediately provided, the patient's family will experience deterioration both psychologically, sociologically and even spiritually. Even though on the one hand, the patient's family is the caregiver for cancer patients, on the other hand, the patient's family also needs support and support from other parties so that the cancer patient and the patient's family together can face this condition. So pastoral care and counseling services are not only an important need for cancer palliative patients but also an important need for the patient's family. This article aims to explain the importance of pastoral care and counseling services for palliative cancer patients and their families. The author will use Jocob Daan Engel's Indonesian theory of mentoring and counseling and Howard Clinebell's theory of pastoral counseling and community counseling. The descriptive qualitative method was used by the author to explain the social psychological conditions of cancer palliative patients and the pastoral care and counseling that is really needed by cancer palliative patients and the patient's families at Church X. Data collection techniques were carried out using observation, interviews and documentation.